PENGARUH SISTEM AKUNTANSI KEUANGAN DAERAH DAN STANDAR AKUNTANSI PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH - Hadi Jauhari; Evada Dewata dewata; Suhairi Hazisma (Universitas Serang Raya, 2021)
This research explores the influence of government accounting standards and regional financial accounting systems as important factors that must be considered in preparing financial reports that are in synergy with the role of the internal control system. The population of this study are employees who work at the Regional Financial and Asset Management Agency (BPKAD) of South Sumatra Province, Indonesia. The sampling technique was purposive sampling and obtained 46 respondents who filled out the questionnaire completely. The regression analysis model used is Moderated Regression Analysis (MRA). The results showed that partially, the application of government accounting standards and regional financial accounting systems had a significant positive effect on the quality of government financial reports, but The government internal control system did not moderate the influence between government accounting standards and the regional financial accounting system on the quality of local government financial reports. The implication of the research is that to achieve the quality of relevant and reliable government financial reports, it is necessary to be consistent in presenting financial statement information following government accounting standards and the regional financial accounting system must be able to integrate regional financial statements comprehensively.